The Existence of Parenting Patterns Based on Local Javanese Values in Lampung Province (Historical Review and Development) - Hidayat, Bobi; Sinaga, Risma Margaretha (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The purpose of this paper is to find out how the Javanese parenting pattern in Lampung Province is felt by today's children and what shifts have occurred in the Javanese parenting pattern in Lampung from the Javanese community parenting pattern to the present. The research method used is a qualitative descriptive method. The data analysis used is a percentage. The research sample was taken using the purposive sampling method on students at Muhammadiyah University of Metro. The data collection methods used include interviews and questionnaires distributed using the help of Google Form and instruments developed using a Likert scale.The results of the study show that the Javanese parenting model in Lampung Province in several aspects still exists, such as meeting the appropriate needs of children, educating children with affection and without punishment, training manners, giving gifts for children's success and giving direction to children for the actions they will take. Meanwhile, in several aspects that have shifted, among others, they no longer scare children about their future with current actions and do not often punish children when they make mistakes. In addition, the use of language uses Javanese and the national language of Indonesia in everyday communication at home.